Therapeutic Effectiveness of Interferon-α2b against COVID-19 with Community-Acquired Pneumonia: The Ukrainian Experience - Kamyshnyi, A.; Koval, H.; Kobevko, O.; Buchynsky, M.; Oksenych, V.; Kainov, D.; Lyubomirskaya, K. S.; Kamyshna, I.; Potters, G.; Moshynets, O.; Любомирська, Катерина Сергіївна (My University, 2023)
Despite several targeted antiviral drugs against SARS-CoV-2 currently being available, the application of type I interferons (IFNs) still deserves attention as an alternative antiviral strategy. This study aimed to assess the therapeutic effectiveness of IFN- in hospitalized patients with COVID-19- associated pneumonia. The prospective cohort study included 130 adult patients with coronavirus disease (COVID-19). A dose of 80,000 IU of IFN- 2b was administered daily intranasally for 10 days. Adding IFN- 2b to standard therapy reduces the length of the hospital stay by 3 days (p < 0.001). The level of CT-diagnosed lung injuries was reduced from 35% to 15% (p = 0.011) and CT injuries decreased from 50% to 15% (p = 0.017) by discharge. In the group of patients receiving IFN- 2b, the SpO2 index before and after treatment increased from 94 (92–96, Q1–Q3) to 96 (96–98, Q1–Q3) (p < 0.001), while the percentage of patients with normal saturation increased (from 33.9% to 74.6%, p < 0.05), but the level of SpO2 decreased in the low (from 52.5% to 16.9%) and very low (from 13.6% to 8.5%) categories. The addition of IFN- 2b to standard therapy has a positive effect on the course of severe COVID-19.
Keywords: IFN-a2b; COVID-19; therapeutic effectiveness; hospital stay; SpO2; CT-diagnosed lung injuries